Electrochemical behavior of the synthetic food diazo dye Brilliant Black BN (E151) and the first voltammetric method for its determination - Dmukhailo, Andrii; Tvorynska, Sofiia; Trukhym, Maksym; Dubenska, Liliya (Talanta, 2025)
As synthetic food azo dyes have been proven to cause adverse health problems, their content is regulated and must be strictly controlled. Therefore, the availability of reliable as well as simple and cost-effective methods for their determination is essential to ensure the quality and safety of food and beverages. This work reports on a systematic study of the electrochemical behavior of Brilliant Black BN (BB BN), a purple synthetic food diazo dye, labelled as E151, in aqueous media using polarography/cyclic voltammetry over a wide range of pH and scan rates. In particular, the electrochemical reduction of BB BN was investigated using a dropping mercury electrode, while the BB BN oxidation - using a glassy carbon electrode. Importantly, this work describes the development of the very first voltammetric method for the determination of BB BN, which is based on its reduction in the Britton-Robinson buffer, pH 3.0, at two types of silver solid amalgam electrodes (AgSAEs), such as polished (p-AgSAE) and mercury meniscus modified one (m-AgSAE). The results demonstrated that the linear scan adsorptive stripping voltammetry in combination with m-AgSAE allows to reach a limit of detection of 0.12 μM applying the accumulation time of 300 s in unstirred solution. The newly developed method was successfully utilized for the direct determination of BB BN in spiked tap water, spiked soft drink, and pharmaceuticals. According to the Blue Applicability Great Index metric tool, the proposed method scored 72.5 points, indicating its suitability in terms of practicality and applicability.
Keywords: Silver solid amalgam electrodes; Electrochemical behavior; Food diazo dye; Linear scan adsorptive stripping voltammetry; Brilliant Black BN